2009
DOI: 10.1002/eji.200839053
|View full text |Cite
|
Sign up to set email alerts
|

Increased numbers of thymic and peripheral CD4+ CD25+Foxp3+ cells in the absence of CD5 signaling

Abstract: It has been suggested that high affinity/avidity interactions are required for the thymic selection of Treg. Here, we investigated the role of CD5, a negative regulator of TCR signaling, in the selection and function of ''naturally occurring'' CD4 1 CD25 1 Treg (nTreg). Analysis of CD5 À/À mice showed a significant increase in the percentage and absolute numbers of CD4 1 CD25 1 Foxp3 1 thymocytes and peripheral T lymphocytes, compared with BALB/c mice. Thymi from CD5 À/À mice showed reduced cellularity due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 78 publications
2
54
2
Order By: Relevance
“…Unexpectedly, individual mutations of the cytoplasmic tyrosines of CD5 did not result in an enhanced activation of Caspase 3 ( Fig. 3C and D), in contrast to the result with Annexin V staining and to our previous report in CD5 À/À mice [17]. This could be explained by differences in sensitivity of apoptosis detection between active Caspase 3 and Annexin V staining or might indicate different detection kinetics.…”
Section: Simultaneous Deletion Of Y429 Y441 and Y463 Results In Enhacontrasting
confidence: 74%
See 3 more Smart Citations
“…Unexpectedly, individual mutations of the cytoplasmic tyrosines of CD5 did not result in an enhanced activation of Caspase 3 ( Fig. 3C and D), in contrast to the result with Annexin V staining and to our previous report in CD5 À/À mice [17]. This could be explained by differences in sensitivity of apoptosis detection between active Caspase 3 and Annexin V staining or might indicate different detection kinetics.…”
Section: Simultaneous Deletion Of Y429 Y441 and Y463 Results In Enhacontrasting
confidence: 74%
“…Previous work by our group demonstrated that thymocytes from CD5 À/À mice display enhanced apoptosis, as demonstrated by Annexin V/7-AAD staining, which correlated with an increased percentage of thymocytes expressing the active form of Caspase 3 [17]. Therefore, we analyzed activation of Caspase 3 in the EL4 clones expressing the different hCD5 mutants (Fig.…”
Section: Simultaneous Deletion Of Y429 Y441 and Y463 Results In Enhamentioning
confidence: 96%
See 2 more Smart Citations
“…CD5 expression is notably higher in T-cell subpopulations with regulatory or suppressive functions, i.e. in regulatory T (Treg) cells [41] suggesting that it may regulate their generation and/or function [42][43][44]. Similarly, CD5 is also highly expressed by regulatory B (Breg) cells [45], in which CD5 expression is required for autocrine IL-10 production.…”
Section: Cd5: a Negative Modulator Of Immune Responsesmentioning
confidence: 99%